2023
DOI: 10.1039/d2nr06421a
|View full text |Cite
|
Sign up to set email alerts
|

Non-〈111〉-oriented semiconductor nanowires: growth, properties, and applications

Abstract: In recent years, non-<111>-oriented semiconductor nanowires have attracted increasing interest in fundamental research and promising applications due to their outstanding crystal quality and distinctive physical properties. Here, a comprehensive overview...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 211 publications
0
10
0
Order By: Relevance
“…In group II-VI and III-V binary semiconductor NW systems, due to the crystal polarity of the material and the combination of low energy and high symmetry of the [111] direction, the ZnSe NWs tend to grow in a zincblende cubic structure along the [111] direction 56 . However, in recent years, non-[111]-oriented semiconductor NWs have attracted increasing interest in terms of fundamental research and promising applications due to their outstanding crystal quality and distinctive physical properties [57][58][59] . Introducing numerous growth techniques, (1) Firstly, we investigate the significance of crystal orientation on the stress-strain response behavior of the zinc-blende ZnSe NWs.…”
Section: Resultsmentioning
confidence: 99%
“…In group II-VI and III-V binary semiconductor NW systems, due to the crystal polarity of the material and the combination of low energy and high symmetry of the [111] direction, the ZnSe NWs tend to grow in a zincblende cubic structure along the [111] direction 56 . However, in recent years, non-[111]-oriented semiconductor NWs have attracted increasing interest in terms of fundamental research and promising applications due to their outstanding crystal quality and distinctive physical properties [57][58][59] . Introducing numerous growth techniques, (1) Firstly, we investigate the significance of crystal orientation on the stress-strain response behavior of the zinc-blende ZnSe NWs.…”
Section: Resultsmentioning
confidence: 99%
“…15,19,51 However, because of their excellent crystal superiority and unique physical features, other orientational semiconductor NWs have gained growing interest in basic research and prospective applications. 52–54 The selective growth of stacking fault-free ZnTe NWs along [100], [110], and [112] crystal orientations is reported using a variety of growth processes, including molecular beam epitaxy and the vapor–liquid–solid growth processes. 55,56 Prior studies also revealed that by maintaining cross-linking among the NWs length, diameter, and growth conditions, NWs can be grown along any of these [110], [100], [112], or [111] four orientations, which are confirmed by X-ray diffraction, photoluminescence spectroscopy, and transmission electron microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…55,56 Prior studies also revealed that by maintaining cross-linking among the NWs length, diameter, and growth conditions, NWs can be grown along any of these [110], [100], [112], or [111] four orientations, which are confirmed by X-ray diffraction, photoluminescence spectroscopy, and transmission electron microscopy. 52,54,57 Realizing the mechanical properties and fracture behavior of ZnTe NWs grown along the [100], [110], and [111] orientations is thus essential for creating and enhancing their uses in various fields, such as NEMS and nanoelectronics.…”
Section: Resultsmentioning
confidence: 99%
“…Combining disease-specific protein corona with sensor array technology offers new thoughts for implementing the strategy. [121] Caracciolo et al constructed a sensor array platform based on diseasespecific protein corona for disease detection using plasma samples. The biomolecular fingerprint could discriminate among five cancers and healthy patients with more than 99% accuracy (n = 90) and even detect a disease early in its development.…”
Section: Non-specific Enrichment Of Proteinsmentioning
confidence: 99%